Critical Review of Sampling Procedures in the Context of Sierra Leone's Low Literacy (and Under-resourced) Research Communities - Emerson Abraham Jackson (Economic Insights - Trends and Challenges, 2018)
This article has provided a critical review of sampling procedures in the context of Sierra Leone. The basics of the two major types of sampling procedures (probability and non-probability) have been explained, with a view of shedding light on their usage to assist researchers in their pursuance of addressing proposed hypothetical statements. Problems associated with low literacy rate in Sierra Leone have been highlighted as a major concern, more so in the process of ensuring ethical code of conducts are adhered to during the execution of sampling research. Research practices in the country needs a complete overhaul, particularly with its very low investment in 'Higher Education Institutions (HEIs)' to help support the backbone of research, and backed by investment in technology to assist with the enhancement of exploring sampling data in pursuit of addressing hypothetical postulates / research questions during research. – – Cet article a fourni un examen critique des procédures d'échantillonnage dans le contexte de la Sierra Leone. le les bases des deux principaux types de procédures d'échantillonnage (probabilités et non probabilités) ont été expliqué, en vue de faire la lumière sur leur utilisation pour aider les chercheurs à poursuivre aborder les propositions d'hypothèses. Problèmes associés au faible taux d'alphabétisation en Sierra Leone ont été mises en évidence comme une préoccupation majeure, plus encore dans le processus visant à garantir un code de conduite éthique sont respectées lors de l'exécution de la recherche d'échantillonnage. Les pratiques de recherche dans le pays ont refonte complète, en particulier avec son très faible investissement dans les «établissements d'enseignement supérieur (EES)» pour aider à soutenir la colonne vertébrale de la recherche, et soutenu par des investissements dans la technologie pour aider à la amélioration de l'exploration des données d'échantillonnage en vue d'aborder des postulats / recherches hypothétiques questions pendant la recherche.
Keywords: B49; C80; C83; 330; Research Methods; Sampling; Ethical Issues; Sierra Leone